Sengketa Hak Kepemilikan terhadap Tanah yang Bergeser Pasca Bencana dalam Tinjauan Hukum Islam: Ownership Rights Dispute Against the Soil Shifts Post Disaster in a Review of Islamic Law - Rosmita, Rosmita; Fitriani, Fitriani; Nasaruddin, Nasaruddin (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2024)
This research aims to determine the process of resolving disputes over land that has shifted after a natural disaster and the law on ownership rights. This research uses a type of library research. This research is included in the qualitative research category with data collection techniques by conducting a review study of books, literature, notes and reports that are related to the problem. From the results of this research, if a land dispute occurs among the community, the dispute resolution process is carried out with two options, carried out through the courts or carried out outside the courts. Settlement through court takes quite a long time to complete. Settlement carried out outside of court is carried out by making peace between the parties to the dispute. Methods outside of court are much more effective in resolving disputes without leaving wounds in the opponent's heart. Islam shows that dispute resolution should be done outside of court. Ownership rights to land that is shifted after a disaster remain the property of the community. It will not be transferred to the government or other communities because after the disaster the government tries to review the land ownership rights of each affected family and re-measure the land directly in the field. But several natural disasters caused property rights to be returned to the government. One of them is abrasion, the cause of abrasion is causing land to be destroyed due to natural factors for which the State is not held responsible.